Experimental and numerical investigation of the trajectories of free and pressurized jets through storage dams - Ali Taheri Aghdam; Farzin Salmasi; Ali Hossein Zadeh Dalir; Akram Abbaspour; John Abraham (Water Supply, 2023)
The purpose of this study is to investigate the trajectories of pressurized and free-falling jets and to determine their location downstream of the dam. The results show that the measured jet trajectory and the values extracted from the jet projectile equations are not the same. This discrepancy may be due to the effect of air resistance on flow; the existing jet trajectory equations do not incorporate air resistance. Projectile equations used for calculating the trajectory of falling jets have an average error of 21 and 26% for free-falling and pressurized jets, respectively. To minimize this discrepancy, the projectile equations were corrected. Also, the numerical simulation predicts the trajectories of the free and pressurized jets on average with a relative error (RE) of 25.5 and 23.5%, respectively, compared to the laboratory data. These errors can be caused by neglecting the effect of air resistance. In addition, it was found that by increasing the Froude number, the location of the falling jet impact moves further from the dam toe. HIGHLIGHTS Impinging jets can cause a wide variety of problems in a water system.; By increasing the diameter of the dam outlet, the location of jet impact approaches the dam toe.; With increasing discharge at a fixed diameter, the impact of the pressurized jet moves further from the dam toe.;